Studi Literatur: Penggunaan Software GeoGebra Untuk Meningkatkan Kemampuan Berpikir Komputasi Siswa Pada Pembelajaran Matematika - Atika Rahmah; Yahfizham (Journal of Student Research, 2024)
In the 21st century, technological development is increasingly rapid and tends towards digitalization, when compared to a few decades ago. So, if it is not utilized, it will be something in vain. Using technology-based learning media will facilitate the learning process, so that it can improve the quality of learning and can improve students' mathematical representation skills. One of the technology-based mathematics learning media that can help students in representing mathematical models/problems is GeoGebra Software. The purpose of this research activity is to find out whether the use of GeoGebra software media can improve students' computational thinking skills in mathematics learning. Improving students' understanding of how to show a model or mathematical problem in graph form or vice versa is one of the benefits of research. The method used in this study is Systematic Literature Review (SLR). This research method is carried out by reviewing journals in a structured manner with predetermined steps. The result of this research activity is that GeoGebra can help students understand the concept of straight line graphs in more detail with a varied and attractive appearance. In addition, for teachers themselves, GeoGebra can be used as a mathematics learning tool to create interactive learning that allows students to explore various abstract mathematical concepts.